Level of Anxiety among Undergraduate Students of Major Public Sector Dental and Medical Colleges, Peshawar - Zahidullah Khan; Inamullah Khan; Zahid Muhammad Wazir; Abdul Khaliq; Zahid Fida; Iqbal Haider (JLUMHS, 2022)
OBJECTIVE: To find out the level of anxiety among undergraduate students of major public sector dental and medical colleges in Peshawar METHODOLOGY: This cross-sectional, descriptive study was conducted in two public sector hospitals, Khyber Medical College and Khyber College of Dentistry Peshawar, before their annual objective structured clinical examination (OSCE) from March to April 2021. Institutional ethical permission was granted through IREB Ethical approval Certificate. Students of MBBS and BDS were included in the study. Students with any psychiatric illness or thyroidal illness taking medications were excluded. Nonprobability convenience sampling technique was used for sample collection. A validated and pretested generalized anxiety disorder (GAD) 7 scale was used to measure anxiety. Results were analyzed using SPSS version 20. A P- value of less than 0.05 was considered significant. RESULTS: Out of 342 students, 333 (223 MBBS and 110 BDS) were enrolled in the study. Nine students were excluded from the study. One hundred and eighty-eight were male, and 145 were female. The mean age was 23.54±1.98 SD years. Nighty six (28.8%) students had minimal anxiety, 100 (30%) had mild anxiety, 75(22.5%) had moderate anxiety, and 62(18.6%) had severe anxiety. There was a significant difference in anxiety levels of both genders (P-value ≤ 0.001). With a cut-off value of ≥10, 138 (41.4%) had a diagnosis of GAD. There was no significant difference in anxiety levels of MBBS and BDS students (Pvalue 0.073). CONCLUSION: Generalized anxiety disorder affects a large population of medical students, affecting female students more than males.